Aniline concentration-dependent surface area of emeraldine salt polyaniline. Issue 6 (March 2021) - Ayuningsih, A; Budi, S; Paristiowati, M; Fahdiran, R; Handoko, E; Sugihartono, I
Abstract: In this paper, we have reported a study on the surface area of emeraldine phase polyaniline prepared from different concentration of aniline. Polyaniline was prepared using oxidative polymerization at low temperature. A Fourier infrared spectrometer and X-ray diffractometer were used to confirm the formation of the conductive phase of polyaniline. The Brunner-Emmet-Teller (BET) surface area of polyaniline was obtained at a relatively low concentration of aniline. The highest BET value was 611.88 m 2 /g.